Simulation of Southwest monsoon current circulation and temperature in the East Coast of Peninsular Malaysia - Farshid Daryabor,; Fredolin Tangang,; Liew, Juneng (Universiti Kebangsaan Malaysia, 2014)
This study investigates the southwest monsoon circulation and temperature along the east coast of Peninsular Malaysia by using the Regional Ocean Modeling System at 9 km resolution. The simulated circulation shows strong northward flowing western boundary currents along the east coast of Peninsular Malaysia with maximum speed of approximately of 0.6-0.7 ms-1. The western boundary current, that extends to a depth of about 35 m, continues flowing northward up to approximately 7oN where it changes direction eastward. The circulation along the east coast of Peninsular Malaysia is also characterized by two anti-cyclonic eddies. Furthermore, an elongated of cooler sea surface temperature that stretches along the coast was also simulated. The existence of this cool SST pattern is associated with coastal upwelling process due to localized lifting of isotherms near the coast as a response to the southerly-southwesterly wind stress along the coast during the southwest monsoon.